Technik und Gender : Technikzukünfte als geschlechtlich codierte Ordnungen in Literatur und Film - Adam, Marie-Hélène [Hrsg.]Schneider- (Karlsruher Studien Technik und Kultur / Hrsg.: G. Banse, A. Böhn, A. Grunwald, K. Möser, M. Pfadenhauer, 2016)
Fictionally depicted technology appears to be dominated by gender stereotypes that reproduce common clichés and are based on the opposition of traditional, gender-associated characteristics. Thus, masculinity represents the technological principle whereas femininity is associated with the sphere of nature. But how stereotypical are visions of a future worlds involving innovative technology? The volume focuses on the gender-codification of technological futures in literature and film.